The Land Commenda in the Late Medieval Crown of Aragon and the Rise of a ‘Democratic’ Investment Culture - Fynn-Paul, Jeff (TSEG - The Low Countries Journal of Social and Economic History, 2018)
This paper presents evidence for the use of the ‘commenda’ contract as a means of investment and accumulating entrepreneurial capital in the Bages region of Catalonia during the later thirteenth and fourteenth centuries. This use of a ‘land commenda’ in eastern Iberia is at present known only to a few specialists, but it might have been more widespread and deserves further study. The land commenda helped fuel the commercial boom in Catalonia in the decades around 1300. It was often utilized by smaller investors and modest entrepreneurs, and helped mobilize capital from a broad spectrum of Catalans. The chronology of land commenda use suggests that as interest rates declined in the later fourteenth century, and as new instruments were developed, smaller investors’ savings were left underutilized.